Basics of digitization - Sanjeev Kumar (Ess Ess Publishers, 2017)
This book is presented with a motive of developing a complete solution for enabling librarians and information professionals to convert print documents to digital form. Recent trends in the information profession shows a growing need for the digital versions of manuscripts, rare books, theses, and dissertations to be made available in various libraries and information centers. But the professionals involving themselves in these new tasks do not have the proper knowledge and expertise. Therefore, a solution for digital preservation is needed so that library professionals performing the process of digitization will have quality assurance over the technical issues of digital preservation. This book focuses on the relevant theory and practice-based issues of digital preservation for libraries. It is divided into four sections: digitization basics; digitization tools; digitization process; and digital file management system, which deals with digital file management system like DSpace, Green Stone Digital Library, FEDORA, and more. Also included is information on the Digital Curation, Web Archiving, evolution of digital preservation, security issues of Digital Right Management, and the various types of formats of digital files, including their suitability for specific type of document or information. [Subject: Library & Information Science, Digitization]